From digital world to real life: a robotic approach to the esophagogastric junction with a 3D printed model - Marano, Luigi (BMC Surg, 2019)
BACKGROUND: Three-dimensional (3D) printing may represent a useful tool to provide, in surgery, a good representation of surgical scenario before surgery, particularly in complex cases. Recently, such a technology has been utilized to plan operative interventions in spinal, neuronal, and cardiac surgeries, but few data are available in the literature about their role in the upper gastrointestinal surgery. The feasibility of this technology has been described in a single case of gastroesophageal reflux disease with complex anatomy due to a markedly tortuous descending aorta. METHODS: A 65-year-old Caucasian woman was referred to our Department complaining heartburn and pyrosis. A chest computed tomography evidenced a tortuous thoracic aorta and consequent compression of the esophagus between the vessel and left atrium. A “dysphagia aortica” has been diagnosed. Thus, surgical treatment of anti-reflux surgery with separation of the distal esophagus from the aorta was planned. To define the strict relationship between the esophagus and the mediastinal organs, a life-size 3D printed model of the esophagus including the proximal stomach, the thoracic aorta and diaphragmatic crus, based on the patient’s CT scan, was manufactured. RESULTS: The robotic procedure was performed with the da Vinci Surgical System and lasted 175 min. The surgeons had navigational guidance during the procedure since they could consult the 3D electronically superimposed processed images, in a “picture-in-picture” mode, over the surgical field displayed on the monitor as well as on the robotic headset. There was no injury to the surrounding organs and, most importantly, the patient had an uncomplicated postoperative course. CONCLUSIONS: The present clinical report highlights the feasibility, utility and clinical effects of 3D printing technology for preoperative planning and intraoperative guidance in surgery, including the esophagogastric field. However, the lack of published data requires more evidence to assess the effectiveness and safety of this novel surgical-applied printing technology.